Numerical and Experimental Investigation of Solar Air Collectors Performance Connected in Series - J.M. Jalil; K.F. Sultan; L.A. Rasheed (Engineering and Technology Journal, 2017)
In the present work, the investigation on the performance of series of solar air collectors to obtain high temperature air was performed. The first collector has been studied experimentally, while the rest of the series collectors have been investigated numerically with the same boundary conditions. The experimental and numerical results of the first collector show acceptable accruement, this lead to calculate the series of collectors numerically. The results indicated that collector’s series do not work with the same efficiency. The first collector will work at low inlet air temperatures, which lead to increase in the efficiency, on the contrary for the other collectors. The results showed that, it can be determined the required number of collectors in series that necessary to obtained the required outlet air temperature.